The Media in the Times of the Coronavirus (COVID-19) Pandemic - Gapsiso, Nuhu Diraso; Garba, Hajara Ibrahim (The Journal of Society and Media, 2023)
The media became a strong driver of either reliable information or misinformation. The trends of issues during the pandemic indicate that media has been targeted by global health authorities, national governments, and health agencies, among other developmental vital stakeholders, in mobilizing the public at all levels to communicate the preventive measures, symptoms, and non-surgical and hygiene practices that would help in stemming the spread of the virus. The paper indicates that knowledge plays a significant role in driving public health practices. Another critical role the media plays in influencing public perception, opinions, attitudes, and behaviors during the peak of the public health emergency. Media also performed the responsibility of being the watchdog of society through consistent follow-ups on contact tracing, daily broadcasts of the infected, recoveries, and fatalities in different countries across the globe, including Nigeria. The paper recommends that the media should be more watchful in the information they disseminate to the public to avoid jeopardizing the primary aim of reducing people's uncertainty. This can be done by controlling information overload by deploying more instruments of gatekeeping to titrate the kinds of information they send through their channels